Comparative efficacy of individual and combined anti-parasitic treatments for Argulosis control - Pujadebi Bera; Santosh Kumar Udgata (Indian Journal of Fisheries, 2025)
Argulus species have emerged as a major challenge in aquaculture, significantly impacting fish health and farm productivity. A survey in fish farms of Ganjam District, Odisha revealed widespread infestation by Argulus siamensis and Argulus bengalensis. Among the two species, A. siamensis exhibited higher prevalence, abundance and infection intensity. Two anti-parasitic drugs viz., Cypermethrin (immersion) and Emamectin benzoate (oral through feed) were selected for both individual and combined use to control infection by A. siamensis. For individual applications, Cypermethrin was administered at 0.94 μg l-1, 2.84 μg l-1, while Emamectin benzoate was provided through feed at 161.41 μg kg-1 and 484.23 μg kg-1. In the combined treatment, alternating doses of both drugs were used. In fishes experimentally infected with A. siamensis, parasite mortality rates recorded were 74 and 87.2% against doses of Cypermethrin at 0.94 μg l-1 and 2.84 μg l-1 respectively, after 48 h of treatment. For Emamectin benzoate, parasite mortality rates observed were 81 and 88% respectively at doses of 161.41 and 484.23 μg kg-1 feed. Combined treatment demonstrated better efficacy, with 100% parasite mortality observed 48 h post-treatment using 2.84 μg l-1 Cypermethrin and 161.41 μg kg-1 Emamectin benzoate in feed. In a farm trial to evaluate the efficacy, this dosage was found effective for complete eradiation (100% reduction) of the parasite within seven days post-treatment. Keywords: Argulus bengalensis, Argulus siamensis, Cypermethrin, Emamectin benzoate